IL-Y Aggravates Murine Chronic Graft-Versus-Host Disease by Enhancing T and B Cell Responses - Wan, Li; Jin, Ziqi; Hu, Bo; Lv, Kangkang; Lei, Lei; Liu, Yonghao; Song, Yuan; Zhu, Ying; Gong, Huanle; Xu, Mimi; Du, Yuanyuan; Xu, Yang; et al. (Frontiers in Immunology, 2020)
IL-Y, a synthetic member of IL-12 cytokine family, was found to exert potent immunosuppressive effects by inhibiting the differentiation and activation of Th1 and Th17 cells. However, the role of IL-Y in the development of chronic graft-versus-host disease (cGVHD) remains unknown. Here, using murine models of scleroderma-like and lupus-like cGVHD, we examined the function of IL-Y in the pathogenesis of cGVHD by hydrodynamically injecting minicircle-IL-Y expressing plasmids (MC IL-Y). In contrast with the reported immune suppressive function of IL-Y, administration of MC IL-Y enhanced cGVHD severity reflected by deteriorated multi-organ pathologic damages. In lupus-like cGVHD model, urine protein and the serum anti-dsDNA antibody (IgG) were significantly upregulated by IL-Y treatment. Further study demonstrated that IL-Y impacts both donor T and B cell response. In T cells, IL-Y inhibited the generation of CD4+Foxp3+ regulator T (Treg) cells during the development of cGVHD. IL-Y may also increase the infiltration of pathogenic TNF-α producing CD4+ and CD8+ T cells through IL-27Rα in recipient spleens, as this effect was diminished in IL-27Rα deficient T cells. Moreover, IL-Y enhanced the differentiation of ICOS+ T follicular helper (Tfh) cells. In B cells, the percentage of germinal center (GC) B cells in recipient spleens was significantly upregulated by MC IL-Y plasmid administration. The levels of co-stimulatory molecules, MHC-II and CD86, on B cells were also enhanced by IL-Y expression. Taken together, our data indicated that IL-Y promoted the process of cGVHD by activating pathogenic T and B cells.